The role of applying achievement accounting in measuring operational efficiency in Palestinian industrial companies - Mohanna, Mohammad Fathi (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the role of the application of achievement accounting in measuring operational efficiency in Palestinian industrial companies according to the areas (accounting for achievement margin, accounting for operating costs, accounting for completion rate), and to achieve the goal The study used the descriptive analytical correlative approach, and a questionnaire consisting of (30) items was prepared, and the questionnaire was distributed to all employees in industrial companies in Palestine, and their number was (16530) male and female employees, and (300) of them were selected as a sample to conduct the study on. SPSS program for analyzing study information.The study reached several results, the most important of which are:There is a direct correlation between the role of implementing achievement accounting and measuring operational efficiency in Palestinian industrial companies in Palestine, which means that the greater the role of implementing achievement accounting (margin of achievement, operating costs, completion rate), the greater the degree of measurement of operational efficiency in industrial companies. Palestinian Territory.After reaching the results, the study recommends the following:The necessity for Palestinian industrial companies to apply the accounting margin of achievement through the development of efficient cost systems by providing all the necessary information for accounting for achievement and costs of the life cycle of products.The need for Palestinian industrial companies to control operating costs in all manufacturing and production processes, by setting special standards for production for all its stages.
Keywords: Achievement Accounting; Completion margin; operating costs; completion rate; operational efficiency